Pemanfaatan Karbon dari Kulit Buah Kelor (Moringa oleifera) untuk Penjernihan Minyak Jelantah - Novela, Riana; Zainul, Rahadian; Kurniawati, Desy; Pernadi, Niza Lian; Rahmi, Maulidia Arsyta; Istiqamah, Siti Sarah; Nizar, Umar Kalmar (Periodic, 2024)
The high demand for cooking oil causes scarcity and increases the price of cooking oil in the market. Despite the scarcity, people still use it by heating it repeatedly. Cooking oil that has been used repeatedly is called used cooking oil which contains saturated fatty acids which will have a negative impact on health if reused. Therefore, this study aims to clarify used cooking oil by using carbon from moringa peels to improve the quality of used cooking oil. Moringa fruit peel contains cellulose and hemicellulose so that it can be used as a carbon source using the calcination method and tested for approximation such as tests for ash content, vapor content and bound carbon. Furthermore, carbon is applied in the clarification of used cooking oil by adsorption method. After the used cooking oil has been clarified, the properties of the used cooking oil are tested, such as density, flow rate, acid number and saponification number. The result of this research is that the resulting Moringa peel carbon at 250 - 350oC complies with the SNI 06-3730-2021 standard. The application of Moringa peel carbon in used cooking oil has been shown to reduce the density value to 0.886 g/mL, an acid number of 4.476 mg/KOH, and succeeded in increasing the value of the flow rate to 0.735 and the saponification number to 351.751 mg/KOH.